Kebijakan Pendidikan Nasional Dalam Perkembangan Kurikulum Di Indonesia - Wicaksono, Juniaris Agung (Ngabari: Jurnal Studi Islam dan Sosial, 2021)
Education is a part of human life which has an important position. The intended interest in this matter is how humans carry out their lives and improve the quality of life. Indirectly if seen based on the philosophy of education which will direct people to think deeply or rooted in the reality of education. The development of national education must also develop in line with global developments by still taking into account the character's cultural values, and also an assessment of conditional factors. The implementation and development of education as intended and expected are in accordance with Law of the Republic of Indonesia Number 20 of 2003. Educational policies and roles that are oriented towards future progress will give birth to quality Indonesians. Qualified humans are humans who have high morale and are intellectual sufficient to know or master science and technology. The new paradigm of education is a new pattern or concept of education to achieve the goals of national education. The purpose of education is to produce human resources capable of facing various future challenges. In essence, the Education Policy that has been made is to improve the quality of education and the welfare of the nation.